Demystifying the Hegemony of the English Language: Scrutiny of ‘Gak Bisa Bahasa Inggris!’ Advertisement within a Semiotics Lens - Sugianto, Ahmad; Prasetyo, Ilham Agung; Aria, Dewi; Wahjuwibowo, Indiwan Seto (Elsya : Journal of English Language Studies, 2022)
Due to its overarching status and power, the English language has dominated and influenced nearly in various means of communication, and one of which is instantiated in advertisements. However, studies concerning the hegemony of the English language represented in an advertisement were found to be under-explored. Thereby, the present study aimed to scrutinise the domination and power of the English language, particularly in Indonesia, represented in one of the advertisements, which is a remake video of a viral video from 2017 to date, entitled ‘Gak Bisa Bahasa Inggris!’ from a Youtube Channel named Pahamy. Semiotic analysis was employed to analyse the advertisement. The findings revealed only five out of eight types of syntagma found comprising descriptive syntagma, bracket syntagma, episodic syntagma, autonomous shot, and scene. The present study concluded that it seemed not possible to have the eight syntagmatic types in a very short advertisement video, and some signs found in the advertisement could be used to shed light on the hegemony of the English language in Indonesia, which might result in either positive or negative effect; hence, any thoughtful consideration and action through multilingual education was advocated to solve or at least mitigate this issue.